2016
DOI: 10.1371/journal.pone.0156710
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Genotyping of Coxiella burnetii and Coxiella-Like Bacteria in Horses in South Korea

Abstract: Coxiella burnetii and Coxiella-like bacteria (CLB) are genetically and ecologically distinct despite some genetic similarities. Furthermore, CLB are exceptionally diverse and widespread in ticks, but rarely detected in domestic animals. Since Coxiella bacteria can be transmitted from infected horses by inhalation or by coming in contact with ticks during activities such as horseback riding, it is necessary to study their prevalence. To the best of our knowledge, this is the first large-scale nationwide investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
54
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 26 publications
5
54
0
Order By: Relevance
“…We previously investigated equine infections in Korea: the seroprevalence of C . burnetii was 1.3% (11/816) and the presence rate of CLE was 0.7% (6/816) [12]. Therefore, another aim of this study was to assess the differences between the C .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously investigated equine infections in Korea: the seroprevalence of C . burnetii was 1.3% (11/816) and the presence rate of CLE was 0.7% (6/816) [12]. Therefore, another aim of this study was to assess the differences between the C .…”
Section: Discussionmentioning
confidence: 99%
“…Over the last few decades, climate changes due to global warming have transformed the Korean climate from temperate to subtropical [12]. This may also explain the spread of Coxiella in vector ticks in Korea.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other Coxiella species have been reported as tick endosymbionts, that are transovarially inherited, and lack virulent characteristics Raele et al, 2015;Seo et al, 2016) and have also been reported in mammals (Angelakis et al, 2016;Seo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%